Optimization of the enzyme-catalyzed synthesis of amino acid-based surfactants from palm oil fractions - Ee, Lin Soo; Salleh, Abu Bakar; Basri, Mahiran; Raja Abdul Rahman, Raja Noor Zaliha; Kamaruddin, Kamarulzaman (Elsevier, 2003)
The feasibility of using palm oil fractions as cheap and abundant sources of raw material for the synthesis of amino acid surfactants was investigated. Of a number of enzymes screened, the best results were obtained with the immobilized enzyme, Lipozyme. The effects of temperature, solvent, incubation period, fatty substrate/amino acid molar ratio, enzyme amount, and water removal on the reactions were analyzed and compared to those on reactions with free fatty acids and pure triglycerides as fatty substrates. All reactions were most efficient when carried out at high temperatures (70–80°C) in hexane as a solvent. However, while reactions with free fatty acids proceeded better when a slight excess of the free fatty acids over the amino acids was used, reactions with triglycerides and palm oil fractions were best performed at equimolar ratios. Also, the addition of molecular sieves slightly enhanced reactions with free fatty acids but adversely affected reactions with triglycerides and palm oil fractions. Although reactions with palm oil fractions took longer (6 d) to reach equilibrium compared to reactions with free fatty acids (4 d) and pure triglycerides (4 d), better yields were obtained. Such lipase-catalyzed transacylation of palm oil fractions with amino acids is potentially useful in the production of mixed medium- to long-chain surfactants for specific applications.